International co-operation in Antarctica: the influence of regional groups. Issue 1 (2nd January 2019) - Colombo, Andrea
ABSTRACT: International co-operation, with the aim to facilitate research in the Antarctic, plays a pivotal role for logistic support and for the deployment of scientific projects run by multiple countries. Co-operative activities can either be intra-continental or external; meaning co-operation based in Antarctica or co-operation that builds on the geographical and political boundaries of every country and governmental policies, respectively. The current situation sees three extra-Antarctic regional groups active in Antarctica, which find their geographical origin, in Asia, Europe and South America. Each group is represented by the Asian Forum for Polar Sciences, the European Polar Board and the Reunión de Administradores de Programas Antárticos Latinoamericanos, respectively, which are operating through their member entities. The Asian Forum for Polar Sciences and the European Polar Board members have demonstrated interest in both the Arctic and Antarctic, and the Reunión de Administradores de Programas Antárticos Latinoamericanos's countries focus their scientific and science-support activities only in the Antarctic Treaty Area. This study analyses the concepts of region and regionalism and how regional co-operations in Antarctica are driving 'big' science projects, which a country might not have the capacity or capability to conduct on its own. It also discusses the breadth, both geographical and biogeographic, that scientific research can obtain through regional co-operation.